Nutrient profile models a useful tool to facilitate healthier food choices: A comprehensive review - Santos, Mariana; Rito, Ana Isabel; Matias, Filipa Nunes; Assunção, Ricardo; Castanheira, Isabel; Loureiro, Isabel (Trends in food science & technology, 2021)
The term “nutrient profile” (NP) has been associated with several concepts arising from the need to regulate the choice of food products, and to allow consumers to make informed and healthier food choices. The use of NP models as a policy tool to improve public health nutrition and reduce the prevalence of non-communicable diseases, is receiving increasing attention. To clarifying the importance of NP models as tools to establish public health interventions concerning consumers’ food choices, a literature review of the guiding principles to implement NP models was conducted. The covered topics include main characteristics, advantages, disadvantages, and associated gaps of the considered NP models. From the selected studies, a total of 85 documents were included. Nutrient profiling has a wide range of applications including front-of-pack (FoP) food labelling, regulation of food marketing to children, regulation of health and nutrition claims and school food standards. Sodium, saturated fatty acids (SFA), and total sugars were the nutrients most frequently to limit; on the contrary fibre was the most used qualifying nutrient. This review gathers, through a holistic approach, the scientific basis behind the development of the NP model, reinforcing the importance of these tools, and enabling regulators with information to establish an appropriate model. •A ‘healthy’ diet requires informed and healthy food choices by the consumers.•Nutrient Profile (NP) models result from the need to promote healthier food choices.•NP models can be a useful tool to help consumers choose healthier food.•Different nutrient profile models are needed for different purposes.•Key points should be considered in the development and sustainable application of NP models.